CONSUMER BEHAVIOR-BASED MARKETING STRATEGY : A STUDY ON INDOSAT OOREDOO USERS IN SURABAYA - Indrawati, Mei; Putra, Allen Pranata; Sama, I Wayan (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the marketing strategy based on consumer behavior of Indosat Ooredoo users in the city of Surabaya. The main focus of the research is to understand consumer behavior in choosing and using telecommunication services, identify factors that influence consumer decisions, and formulate relevant marketing strategies based on consumer preferences and needs. This research uses a qualitative approach with data collection methods in the form of in-depth interviews, observations, and documentation. The informants consist of Indosat Ooredoo consumers and relevant internal parties. The results of the study show that consumer behavior is influenced by preferences for competitive pricing, network stability, service personalization, and digital experience through the MyIM3 application. The main factors that influence consumer decisions include price, network quality, digital innovation, and brand image. Based on these findings, recommended marketing strategies include adjusting data plans for specific market segments, improving network quality, strengthening digital features, and customer service responsiveness. This research has limitations in its limited scope to the city of Surabaya and a qualitative approach that relies on the subjectivity of the informant. Further research with a quantitative approach or a broader scope is recommended to provide a more comprehensive understanding.